2010
DOI: 10.1017/s0954102010000258
|View full text |Cite
|
Sign up to set email alerts
|

Impact of expected global warming on C mineralization in maritime Antarctic soils: results of laboratory experiments

Abstract: This study concerned the fragility of maritime Antarctic soils under increasing temperature, using the C dynamics and structural characteristics of humic substances as indicators. Working with four representative soils from King George Island (Lithic Thiomorphic Cryosol (LTC1 and LTC2), Ornithogenic Cryosol (OG) and Gelic Organosol (ORG)) we evaluated the total organic C and nitrogen contents, the oxidizable C and humic substances. Soil samples were incubated to assess the amount of C potentially mineralizable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This could cause decomposition rates to be higher 8,9 than expected since SOC litter is mainly composed of C derived from cellulose, lipids, and peptides, although incipient humic substances have also been isolated from these soils 10–12 . These results are consistent with studies using cross‐polarization magic angle spinning (CPMAS), nuclear magnetic resonance for C ( 13 C‐NMR), nitrogen ( 15 N‐NMR) spectroscopy, and pyrolysis field‐ionization mass spectrometry (Py‐FIMS) for organic histosols formed from mosses on the Antarctic continental coast in Eastern Antarctica 11,12 and soils formed under similar conditions in Western Antarctica, King George Island 13,14 . Previous research on SOC composition in these environments found carbohydrates and the enrichment of alkyl‐C and showed signals of incipient formation of aromatic structures due to the scarce presence of vascular plants and the lack of lignin, in mosses and lichens 12,13 .…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…This could cause decomposition rates to be higher 8,9 than expected since SOC litter is mainly composed of C derived from cellulose, lipids, and peptides, although incipient humic substances have also been isolated from these soils 10–12 . These results are consistent with studies using cross‐polarization magic angle spinning (CPMAS), nuclear magnetic resonance for C ( 13 C‐NMR), nitrogen ( 15 N‐NMR) spectroscopy, and pyrolysis field‐ionization mass spectrometry (Py‐FIMS) for organic histosols formed from mosses on the Antarctic continental coast in Eastern Antarctica 11,12 and soils formed under similar conditions in Western Antarctica, King George Island 13,14 . Previous research on SOC composition in these environments found carbohydrates and the enrichment of alkyl‐C and showed signals of incipient formation of aromatic structures due to the scarce presence of vascular plants and the lack of lignin, in mosses and lichens 12,13 .…”
Section: Introductionsupporting
confidence: 76%
“…pyrolysis field-ionization mass spectrometry (Py-FIMS) for organic histosols formed from mosses on the Antarctic continental coast in Eastern Antarctica 11,12 and soils formed under similar conditions in Western Antarctica, King George Island. 13,14 Previous research on SOC composition in these environments found carbohydrates and the enrichment of alkyl-C and showed signals of incipient formation of aromatic structures due to the scarce presence of vascular plants and the lack of lignin, in mosses and lichens. 12,13 Therefore, increasing temperatures in Maritime Antarctic soils may cause fast turnover of SOC because readily decomposable organic C has not been extensively mineralized due to cold conditions and the absence of recalcitrant organic compounds.…”
mentioning
confidence: 99%